A Community’s Participation in Migrant Workers Problem Management in Baan Ton Chok, NongBua, ChaiPrakaan District, Chiang Mai - ปัญญาวัน กิตติชัย (Community and Social Development Journal, 2015)
The objective of this qualitative research is to study a community’s participation in the management of migrant workers. It is also a field research and the secondary data was collected by using an in-depth interview, a focus group, group activities and an observation. It is found that the community and the government sectors cooperatively perceived operational problems of the management of the migrant workers which are a lack of cooperation, building up knowledge and understanding, communication and interaction as well as a lack of perception of boundaries of power and authorities. It is then analyzed to create participatory strategies for the operation by creating a model of regularization of migrant workers by virtue of the government sectors basically. After that, a learning process and a method of operation are set by the government sector and the community. The power is collaborated for the operation by defining roles and duties with the community’s own potentiality. This is the external power collaboration. In the meantime, there is the informal internal power collaboration within the community, through socialization, controlling with mores, morality and folkways. The collaboration of various norms and the model of controlling from other sectors, that can operate, support and subserve each other, can lead to more sustainable problem management. Furthermore, an integration of the sectors’ operations is area-based in order to inquire some occurrence and main stakeholders in the community.